2009
DOI: 10.1128/jvi.02674-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Hepatitis C Virus with Defective Genome and Its Infectivity in Vitro

Abstract: Replication and infectivity of hepatitis C virus (HCV) with a defective genome is ambiguous. We molecularly cloned 38 HCV isolates with defective genomes from 18 patient sera. The structural regions were widely deleted, with the 5 untranslated, core, and NS3-NS5B regions preserved. All of the deletions were in frame, indicating that they are translatable to the authentic terminus. Phylogenetic analyses showed self-replication of the defective genomes independent of full genomes. We generated a defective genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 16 publications
(11 reference statements)
3
34
0
Order By: Relevance
“…S1B), a finding consistent with previous reports (4,6,15). Downregulated virus release and reduced production of infectious virus were also observed when the infectious chimeric HCV genome, TNS2J1 (30), which contains the HCV-1b-derived structural region and the JFH1-derived nonstructural region, was examined (see Fig. S1B, right).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…S1B), a finding consistent with previous reports (4,6,15). Downregulated virus release and reduced production of infectious virus were also observed when the infectious chimeric HCV genome, TNS2J1 (30), which contains the HCV-1b-derived structural region and the JFH1-derived nonstructural region, was examined (see Fig. S1B, right).…”
Section: Resultssupporting
confidence: 78%
“…RNA was extracted from 10-times-concentrated HCVcc for real-time reverse transcription-PCR (RT-PCR). Quantitative real-time RT-PCR analysis of the 5Ј untranslated region of the HCV genome was performed as described previously (30). The forward and reverse primers were 5Ј-CCCTC CCGGGAGAGCCATAGTG-3Ј and 5Ј-GTCTCGCGGGGGCACGCCCAAA T-3Ј, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments to elucidate the role of mannose trimming of N-glycans in the HCV life cycle are currently under way. It has recently been demonstrated that subgenomic replicons or defective genomes of HCV that have the potential of translation and self-replication can be encapsidated into infectious viruslike particles by trans-complementation of the viral structural proteins (1,17,32,41,44). In these studies, the viral RNAs were generally generated by in vitro transcription from linearized corresponding plasmids, followed by electroporation into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Detection of HCV infection was performed using quantitative reverse transcription-PCR (qRT-PCR) and immunohistochemistry as previously described. 10,11) HCV Pseudoparticle Infection HCV pseudoparticles (HCVpp) were generated as previously described.…”
Section: Construction Of Retroviral Expression Vectorsmentioning
confidence: 99%